Stool fatty acid soaps, stool consistency and gastrointestinal tolerance in term infants fed infant formulas containing high sn-2 palmitate with or without oligofructose: a double-blind, randomized clinical trial - Nowacki, Joyce (Nutr J, 2014)
BACKGROUND: Formula-fed (FF) infants often have harder stools and higher stool concentrations of fatty acid soaps compared to breastfed infants. Feeding high sn-2 palmitate or the prebiotic oligofructose (OF) may soften stools, reduce stool soaps, and decrease fecal calcium loss. METHODS: We investigated the effect of high sn-2 palmitate alone and in combination with OF on stool palmitate soap, total soap and calcium concentrations, stool consistency, gastrointestinal (GI) tolerance, anthropometrics, and hydration in FF infants. This double-blind trial randomized 165 healthy term infants 25–45 days old to receive Control formula (n = 54), formula containing high sn-2 palmitate (sn-2; n = 56), or formula containing high sn-2 palmitate plus 3 g/L OF (sn-2+OF; n = 55). A non-randomized human milk (HM)-fed group was also included (n = 55). The primary endpoint, stool composition, was determined after 28 days of feeding, and was assessed using ANOVA accompanied by pairwise comparisons. Stool consistency, GI tolerance and hydration were assessed at baseline, day 14 (GI tolerance only) and day 28. RESULTS: Infants fed sn-2 had lower stool palmitate soaps compared to Control (P =0.0028); while those fed sn-2+OF had reduced stool palmitate soaps compared to both Control and sn-2 (both P <0.0001). Stool total soaps and calcium were lower in the sn-2+OF group than either Control (P <0.0001) or sn-2 (P <0.0001). The HM-fed group had lower stool palmitate soaps, total soaps and calcium (P <0.0001 for each comparison) than all FF groups. The stool consistency score of the sn-2+OF group was lower than Control and sn-2 (P <0.0001), but higher than the HM-fed group (P <0.0001). GI tolerance was similar and anthropometric z-scores were <0.2 SD from the WHO growth standards in all groups, while urinary hydration markers were within normal range for all FF infants. CONCLUSIONS: Increasing sn-2 palmitate in infant formula reduces stool palmitate soaps. A combination of high sn-2 palmitate and OF reduces stool palmitate soaps, total soaps and calcium, while promoting softer stools. TRIAL REGISTRATION: This study was registered on http://www.clinicaltrials.gov: number NCT02031003. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1475-2891-13-105) contains supplementary material, which is available to authorized users.